Shame Memories and Eating Psychopathology: The Buffering Effect of Self-Compassion - Ferreira, Cláudia (2014)
Research suggests that self-compassion may protect against shame in eating disorders. This study examines the association between shame memories, self-compassion, self-judgment and eating psychopathology severity and tests the moderator effect of self-compassion on the relationships between shame memories and eating psychopathology.